Pengembangan Pembelajaran Membaca Berbasis Kearifan Lokal Karapan Sapi Madura untuk Menumbuhkan Sikap Menghargai Keberagaman - Nurhidayatul Masfiyah; Nurul Istiq’faroh; Rizkya Silmi Kaaffah; Muthiah Fidarayni (CV. Kurnia Grup, 2026)
This study was motivated by the low effectiveness of reading instruction in elementary schools, which has not fully linked the material to the students’ sociocultural context, as well as the lack of integration of diversity values into teaching materials. This study aims to develop and test the feasibility of a reading Student Worksheet (LKPD) based on the local wisdom of the Madura Karapan Sapi (Bull Racing) tradition to foster an attitude of mutual respect for diversity. The study employs the Research and Development (R&D) method using a simplified Borg and Gall model, encompassing the stages of needs analysis, design, development, validation, revision, and limited pilot testing. The approach used was a mixed-methods design, with data collected through observation, interviews, questionnaires, and tests. The results of the study showed a significant improvement in students’ reading skills, marked by an increase in the average score from 68.57 to 89.29. Additionally, students demonstrated a more positive attitude toward diversity. Thus, the LKPD based on the local wisdom of the Madura Karapan Sapi is deemed suitable and effective for use as contextual teaching material that not only improves reading skills but also strengthens the development of students’ social character.